Pension Literacy And Saving For Retirement Among Generation X: Evidence From Croatia - Dajana BARBIĆ; Andrea LUČIĆ; Maja GRGEČIĆ (Communications of International Proceedings, 2022)
Individuals are increasingly being encouraged to take responsibility for their financial well-being, particularly their retirement. Therefore, examining pension literacy is critical, since it helps in sustaining financial security during times of financial fragility. This paper investigates pension knowledge, attitudes and private retirement savings among Generation X. It analyzes the importance and provides an overview of pension literacy in Croatia. The results show that pension literacy in Croatia among Generation x is moderate and there is substantial space to improve the level of pension knowledge, attitudes, and particularly, pension behavior.
Keywords: pension literacy; retirement; retirement savings; Generation X